Praktik Politik Uang dalam Pemilihan Kepala Desa Dihubungkan dengan Asas Jujur dan Adil dalam Pemilihan Umum - Malsal Jajuli Haerudin Hermawan; Rini Irianti Sundary (UNISBA Press, 2022)
Abstract. The Village Head Election is a direct election of the village head by local villagers and appointed by the Regent/Mayor. The existence of this village head election as a form of a democratic party as well as a new hope and motivation for the village community, especially the village of Curug Agung. Pilkades in Curug Agung Village is expected to produce village head candidates who care about the people so that they can make a major contribution to the progress of the village. However, in village-level democracy, it is undeniable that there are indications of political violations, namely money politics. So the author conducted a study entitled